Kaizen strategies for winning through people : - Cane, Sheila (Pitman Pub., 1996)
Cane, an experienced writer (Ready-Made Activities for Negotiation Skills, Pitman, 1994), offers an extended explanation of the old concept of kaizen, the Japanese business philosophy of continuous improvement, where the focus is on processes rather than results. A similar look into this philosophy appears in Masaaki Imai's Kaizen: The Key to Japan's Competitive Success (LJ 10/1/86) and other books. The emphasis here is on human relationship skills. Trust, respect, and the ability to admit mistakes are some of the core values of this concept. Cane's premise is that in the West, too much focus is on achieving financial targets and competitiveness and not enough on life skills of communicating and listening as criteria to foster cooperation within organizations. Chapters discuss mentoring, team working, training, and development where people are cross-trained to do different jobs?an important concept in an environment of downsizing and reengineering. Case studies are dispersed throughout, and checklist summaries are at the end of each chapter.